Harijans and the Prospects of their Human Rights - Pushparajan, A (Journal of Dharma, 1983)
The problem of harijans has become a burning issue today in India. It has not only been attracting the attention of journalists and politicians, but it is also agitating the minds of the religious leaders. It has been hitting the headline in various forms : the swift and brutal massacre of 24 harijans in Deoli village, the gunning down of 10 harijans in cold blood in Sadhupur village, the burning down of harijan villages in Ramnad district, Tamilnadu in the early fifties, the most cruel persecution of harijans at Villupuram, in July 1978, the saddest plight in which Bihar harijans have found themselves in the last few years. All these confirm that the problem of harijans is widespread in our country. During the decade 1966—76, according to official reports 40,000 cases of atrocities on harijans were filed in the law courts. And in the year 1976 alone, there were 10,879 cases.